2022
DOI: 10.3390/ijerph19095482
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric–Neonatal Care during Birth and Postpartum in Symptomatic and Asymptomatic Women Infected with SARS-CoV-2: A Retrospective Multicenter Study

Abstract: This study analyses the obstetric–neonatal outcomes of women in labour with symptomatic and asymptomatic COVID-19. A retrospective, multicenter, observational study was carried out between 1 March 2020 and 28 February 2021 in eight public hospitals in the Valencian community (Spain). The chi-squared test compared the obstetric–neonatal outcomes and general care for symptomatic and asymptomatic women. In total, 11,883 births were assisted in participating centers, with 10.9 per 1000 maternities (n = 130) infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
2
4
0
Order By: Relevance
“…The prematurity rate observed in our center was 7.6%, close to the pre-pandemic rate (6.4-7%) [23,33]. We did not find a significant relationship between the outcomes and infection, possibly owing to the small number of cases managed in our hospital; pregnant women with threatened preterm deliveries were referred to the referral hospital, and only deliveries of more than 34 weeks of gestation or preterm babies whose transfer was impossible owing to obstetric conditions of an imminent delivery were managed in our center.…”
Section: Obstetric and Neonatal Outcomes Between Infected And Non-inf...supporting
confidence: 79%
See 2 more Smart Citations
“…The prematurity rate observed in our center was 7.6%, close to the pre-pandemic rate (6.4-7%) [23,33]. We did not find a significant relationship between the outcomes and infection, possibly owing to the small number of cases managed in our hospital; pregnant women with threatened preterm deliveries were referred to the referral hospital, and only deliveries of more than 34 weeks of gestation or preterm babies whose transfer was impossible owing to obstetric conditions of an imminent delivery were managed in our center.…”
Section: Obstetric and Neonatal Outcomes Between Infected And Non-inf...supporting
confidence: 79%
“…Throughout this period, stringent measures were enforced during states of emergency to curb viral transmission [21]. These measures had direct repercussions on the medical care provided to pregnant women, resulting in discernible adjustments to obstetric protocols [22,23]. Scientific societies remained dynamic, continually adapting obstetric care protocols in response to evolving epidemiological trends [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A multicentric cohort study by Oncel et al revealed high rates of cesarean section (71.2%), prematurity (26.4%), and low-birthweight-infant rates (12.8%) for a cohort of patients with COVID-19 [ 42 ]. Another retrospective multicentric study indicated higher rates of NICU admission among offspring of symptomatic women [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…This change also led to strong changes in the care of women during pregnancy, childbirth and the postnatal weeks, and basic elements of the midwife–woman relationship, such as meeting in person and providing a comforting touch, were upended in an attempt to maintain distance and reduce cross-infection [ 24 ]. In Spain, during the first months of the pandemic, the care protocols for women underwent several changes, which meant a high change in the measures to be adopted in maternity services, both for SARS-CoV-2-positive women and for others [ 24 , 25 ] These changes during these first months meant an increase in unnecessary interventions and severe limited visiting, even certain limitations to the labor or postpartum companionship [ 24 ].…”
Section: Discussionmentioning
confidence: 99%